ACCOUNTING AND THE MANAGEMENT OF PUBLIC AFFAIRS. - Andrews, T. Coleman (The Accounting Review, 1947)
Abstract In an excellent article entitled "The Accounting and Treasury Functions in a Modern Organization," J.A. Campbell, a prominent accountant of Chicago, made the very sage statement that the accounting department pays its way by serving the business, not by trying to run it." The author doubts that anyone could frame in fewer words a more accurate and inclusive statement of the fundamental purpose of accounting than was thus expressed by Campbell. The author in this article indicates at least one important way in which accounting can be made to serve business. On the whole, the administration of public affairs does not require the use of involved accounting systems, procedures, or techniques; except in occasional, special situations, the requirements are simple. But many years ago somebody got the idea that the budgeting of income and expenditures called for special methods and techniques, and somehow or other enough public officials fell for the idea to give it a firm foothold. In most businesses the practice as to the classification of expenses is not even to ascertain the expenses of the accounting department as such, let alone the cost of the several activities that constitute the department.